'n Konseptualisering van Kommunikasiebestuursopleiding - JM Groenewald JM Groenewald (Communicare)
Communication Management Training is an unfamiliar concept to some communication scholars. Although there seems to be general agreement on the pragmatic justification and viability of communication training in the management sciences, questions are being asked about the academic legitimacy of Communication Management as educational model. This article sets out to explain communication management training through an analysis of the four communication-focused subject areas that may be legitimately taught in the management sciences. This analysis will be based on a conceptual analytical framework, derived from prior attempts to differentiate communication-related subject fields. To conduct the analysis, the author made use of an exploratory qualitative approach by studying contributions in The Joumal of Business Communication, Management Communication Quarterly, ABC Bulletin, Communication Monographs and Public Relations Review.